The Ability of Non-English Students in Online Learning for TOEFL Course - Arfiawati, Fristi; Juhridin, Juhridin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
The research entitled The Ability of Non-English Students in Online Learning for TOEFL Course at Pasim National University applied the theory from Phillips (2001).  The aim of this research is to investigate the ability of the students of non-English department in learning TOEFL and conducting TOEFL prediction test. In addition, this research used descriptive qualitative method as the students are given the material of TOEFL which include the listening, structure, and reading comprehension and then they are given the prediction test. The research is also used the converted score according to CEFR or Common European Framework of Reference for Language to measure the level of student’s ability.  The data is obtained from 18 non-English students who join online TOEFL Course that comprises into Psychology, Informatic Engineering, Accounting, and Management. The result showed that the ability of students categorized into level A2-Elementary, B1-Intermediate and B2-Upper Intermediate.  In addition, the students of Psychology and Informatic Engineering has a level of A2, B1 and B2 meanwhile other Study Program is still in the level of A2-Elementary.  Thus, the ability of non-English students are still low, and the achievement of level are mostly in level A2-Elementary. There is still low for level B1 and B2. However Psychology and Informatic Engineering has an improvement of achievement level compare to other study programs.  The highest achievement level is level B2 and it is achieved by the student from Psychology and Informatic Engineering.  Therefore, the non-English students of Pasim National University require the improvement of online teaching learning activity of TOEFL to increase the proficiency of English language.